Ukon jäljet paikoissa ja paikannimissä : Tutkimus ukko-elementin sisältävistä nimistä - Aalto, Tiina (Helsingin yliopisto, 2019)
The data of this thesis consists of place names that include the lexical element ukko as a nominative or genitive attribute. The study investigates the types of sites referred to by these names. The locations are described using maps and spatial data. Particular attention is paid to the elevation of the sites and their relationship to water. In addition, the background of the names, i.e. the basis for naming, is discussed with the help of traditional data stored in place name collections. Distribution maps have been prepared for the most important name types included in the material, and the place name data has been extracted from the Names Archive Collection of the Institute for the Languages of Finland (Kotimaisten kielten keskus, KKK) by using the Namesampo workbench. The survey also includes maps using the place name data of the National Land Survey of Finland. Digital spatial data has been used to examine the distribution and other characteristics of place names, the most important of which are the SMS dialect areas (KKK), the National Board of Antiquities' register (Muinaisjäännösrekisteri), the Ancient Shorelines Database of the Geological Survey of Finland, elevation data contained in the Topographic Database of the National Land Survey of Finland and the Ranta10 dataset of the Finnish Environment Institute. The names containing the ukko element are spread throughout the east and focus on Savo and South Karelia. The three most common name types are Ukonniemi, Ukonsuo and Ukonlampi. Names related to land elevations and forests are also numerous. In the study, the topographic features of the Ukonvuori sites are described by examining the elevation of the named sites and their connection to bodies of water. It was observed that there were a few more Ukonvuori sites bordering the lakes and watercourses than those not bordering on them. The oral tradition of place names stored in the Names Archive emphasizes, on the one hand, explanations of the origin of the name in which the place name element ukko refers ...